Effect of ionophore enriched UMMB on feed intake, nutrient utilization and growth of crossbred calves - DE, D; SINGH, G P (The Indian Journal of Animal Sciences, 2014)
Male crossbred calves (20) were divided into 4 groups of 5 each. The animals of groups 1 and 2 were fed concentrate mix. And monensin (30 mg/d/animal) supplemented concentrate mix, respectively, along with ad lib. Wheat straw, while groups 3 and 4 were fed wheat straw ad lib. with 70 % concentrate mix of their requirement and had free access to urea molasses mineral block (UMMB) prepared through cold process with or without ionophore (monensin). Total dry matter (DM) intake, DM intake in terms of per cent body weight and g/kg W0.75 did not differ significantly. Average block consumption in group 3 (358.00 g/day) was higher than in group 4 (243.00 g/day). Nutrient digestibility was similar among, however, CF digestibility was significantly (P